Kinerja Karyawan : Dampak Teknologi Informasi Dan Locus Of Control Dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Mediasi (Survei Pada Karyawan Perumda Pdam Tirtamarta Kota Yogyakarta) - Rahayu Dyah Mawarti; Titi Laras; Nadia Nadia (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Regional Drinking Water Company (PDAM) is a local government company. Bermuda PDAM Tirtamarta must be able to provide the best service to meet the community's clean water needs. This is not easy to achieve without proper human resource management. One of them is to identify the impact of information technology on organizational citizenship behaviour (OCB), the place of control on organizational citizenship behaviour (OCB), and the impact of information technology on team member performance and identify its effects. Identifying areas for controlling team member performance. Recognizing the implications of OCB on team member performance. Placing OCB in mediating the impact of information technology on team member performance. Identifying Organizational Citizenship Behavior (OCB) in Intermediary Management of Perumda PDAM. This study uses probability sampling proportional stratified random sampling with the Slovin formula received by the staff of Perumda PDAM Tirtamarta as many as 1 Three respondents. The data was then processed using the Structural Equalization Model (SEM) analysis tool through the SPSS AMOS version 26 application. Using the Cronbach alpha standard, the validity test was > 0.3, and the reliability test was > 0.7. . Research has shown that information technology has a positive and significant impact on team member organizational citizenship behaviour (OCB). The influence of the control location is positive and significant on team member organization citizenship behaviour (OCB). The positive impact of information technology on team member performance is not substantial. However, the influence of the control location is positive and significant on team member performance. The effect of Organizational Citizenship Behavior (OCB) is positive and effective on the performance of Bermuda PDAM Tirta Malta employees, Yogyakarta City. Organizational Citizenship Behavior (OCB) can communicate the impact of information technology on team member performance. Organizational Citizenship Behavior (OCB) can share the control result on the performance of Perumda PDAM Tirtamarta employees, Yogyakarta City.